Description of four new species of the subgenus Tachycines (Gymnaeta) Adelung, 1902 (Orthoptera: Rhaphidophoridae) from caves in China and additional notes on some previously known species - Zhu, Qi-Di; Shi, Fu-Ming (European Journal of Taxonomy, 2021)
In this paper, four new cave-dwelling species of the subgenus Tachycines (Gymnaeta) from Guangxi, Hunan and Jiangxi are described, i.e., Tachycines (Gymnaeta) quadratus sp. nov., Tachycines (Gymnaeta) shiziensis sp. nov., Tachycines (Gymnaeta) sparsispinus sp. nov. and Tachycines (Gymnaeta) papilious sp. nov. The female of Tachycines (Gymnaeta) liboensis Zhu, Chen & Shi, 2020 is recorded for the first time. Moreover, images illustrating the morphology of the four new and three previously described species are provided.